2018
DOI: 10.2993/0278-0771-38.3.390
|View full text |Cite
|
Sign up to set email alerts
|

Aboriginal Translocations: The Intentional Propagation and Dispersal of Plants in Aboriginal Australia

Abstract: The prevalence and imperative of translocations for the conservation of plant species is increasing in response to habitat loss and degradation, plant diseases, and projected climate change. However, the intentional movement and nurture of plant species to increase their range and/or abundance has been practiced for millennia, encompassing species with food, medicinal, narcotic, and ceremonial values. While it is well documented that Australian Aboriginal people altered the composition and structure of vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Indigenous Australians have occupied the Pilbara for at least 50 thousand years [ 113 ] and may have been important dispersers of some plant species [ 114 ]. Relatively little recognition has hitherto been given to the potential impacts of this means of dispersal on the present distributions of species and their genetic diversity, but it is likely that people have impacted the current biogeography of plant species, mobilising them for their use as food, medicine or for totemic purposes [ 114 , 115 , 116 , 117 ]. Combined with extreme meteorological events, these features provide a context for understanding the LDD observed in widespread Pilbara plant species and can form the basis of future hypotheses regarding genetic connectivity amongst the Pilbara flora.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous Australians have occupied the Pilbara for at least 50 thousand years [ 113 ] and may have been important dispersers of some plant species [ 114 ]. Relatively little recognition has hitherto been given to the potential impacts of this means of dispersal on the present distributions of species and their genetic diversity, but it is likely that people have impacted the current biogeography of plant species, mobilising them for their use as food, medicine or for totemic purposes [ 114 , 115 , 116 , 117 ]. Combined with extreme meteorological events, these features provide a context for understanding the LDD observed in widespread Pilbara plant species and can form the basis of future hypotheses regarding genetic connectivity amongst the Pilbara flora.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Forster (2004) made no mention of human dispersal in discussion of Macrozamia genetic patterns. Conversely, Silcock (2018) suggested that numerous plant translocations are likely to have occurred in at least 50 000 years of Australian human history, but much knowledge of Aboriginal translocations remains undocumented and therefore overlooked or underestimated by contemporary ecologists. Such translocations may account for unusual, disjunct populations in the Australian flora.…”
Section: Discussionmentioning
confidence: 99%
“…It might be argued that this is a misuse of the term 'cultivator', for cultivation entails a suite of related activities including the production and storage of seed (or the equivalent in roots and tubers), preparation of the soil through tillage, etc., sowing or planting, tending crops through such practices as weeding and fencing, harvesting and storage. One might add the importance of translocation in shaping the distribution of food plants (Silcock 2018).…”
Section: The Argument That Aboriginal People Were Farmersmentioning
confidence: 99%